Site investigation of damages occurred in a steel space truss roof structure due to ponding - Piroglu, Filiz; Ozakgul, Kadir; Iskender, Hikmet; Trabzon, Levent; Kahya, Ceyhan (Elsevier BV, 2014)
Abstract In this study, a steel space truss roof structure which was partially collapsed after a local meteorological event that produced strong winds and heavy rains in Marmara region was investigated. For this purpose, damage reconnaissance studies were conducted and findings observed in the site were interpreted according to the current Turkish steel building design codes based on allowable stress design. For the structural members taken from debris, material tests were conducted. This steel space truss roof structure covering an industrial facility was supported on reinforced concrete columns of 11 m height, sheathed by using fibro panel with membrane, having a slope of 1% to monitor the waterflow to the siphonic roof drainage system and surrounded by the parapets of 15 and 25 cm heights at the roof-edges. As a result of the investigation, it was estimated that during this extreme rainfall event, due to any deficiency or blockage of the roof drainage system in the edge zones with parapets of the roof, rainwater accumulation occurred at these regions of the roof fully and eventually due to the ponding which is a particular loading case for the design of the structures that is however not defined by the Turkish design standards, roof collapse of this industrial hall building occurred partially.